Genome-Wide Analysis of the TCP Gene Family and Their Expression Pattern Analysis in Tea Plant (Camellia sinensis) - Shang, Xiaowen; Han, Zhaolan; Zhang, Dayan; Wang, Ya; Qin, Hao; Zou, Zhongwei; Zhou, Lin; Zhu, Xujun; Fang, Wanping; Ma, Yuanchun (Frontiers in Plant Science, 2022)
TCP transcription factors (TEOSINTE BRANCHED1/CYCLOIDEA/PCF) have been suggested to control of cell growth and proliferation in meristems and lateral organs. Thirty-seven CsTCP genes were identified and divided into two classes, class Ⅰ (PCF, group 1) and class Ⅱ (CIN CYC/TB1, group 2 and group 3). The residues of CsTCP proteins between class I and class II were definitely different in the loop, helix I, and helix II regions, however eighteen conserved tandem was found in bHLH. There are a large number of CsTCP homologous gene pairs in three groups. And most CsTCP proteins have obvious differences in motif composition. The results illuminated that CsTCP proteins in different groups are supposed to have complementary functions, while those in the same class seem to display function redundancies. There is no relationship between the number of CsTCP gene members and genome size, and the CsTCP gene family has only expanded since the divergence of monocots and eudicots. WGD/segmental duplication played a vital role in the expansion of the CsTCP gene family in tea plant, and the CsTCP gene family has expanded a lot. Most CsTCP genes of group 1 are more widely and nonspecifically expressed, and the CsTCP genes of group 2 is mainly expressed in buds, flowers and leaves. Most genes of group 1 and some genes of group 2 were up/down-regulated in varying degrees under different stress, CsTCP genes of group 3 basically does not respond to stress. TCP genes involved in abiotic stress response mostly belong to PCF group. Some CsTCP genes may have the same function as the homologous genes in Arabidopsis, but there is functional differentiation.